2021
DOI: 10.1016/j.neubiorev.2021.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Atypical interoception as a common risk factor for psychopathology: A review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 823 publications
(1,127 reference statements)
2
69
1
Order By: Relevance
“…This demonstrates a shift in the aIns processing of threat valence with different levels of anxiety, in line with hypothesized differences in brain prediction processing ( Paulus and Stein, 2006 , 2010 ; Paulus et al., 2019 ). In comparison, no anxiety group differences or interactions were found in the breathing prediction error domain, contrasting with some previously proposed hypotheses ( Barrett and Simmons, 2015 ; Brewer et al., 2021 ; Paulus and Stein, 2006 , 2010 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This demonstrates a shift in the aIns processing of threat valence with different levels of anxiety, in line with hypothesized differences in brain prediction processing ( Paulus and Stein, 2006 , 2010 ; Paulus et al., 2019 ). In comparison, no anxiety group differences or interactions were found in the breathing prediction error domain, contrasting with some previously proposed hypotheses ( Barrett and Simmons, 2015 ; Brewer et al., 2021 ; Paulus and Stein, 2006 , 2010 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Here, we build on these conceptual advances and assess the relationship between anxiety and breathing-related interoception across the multiple hierarchical levels of processing. Importantly, although many theoretical proposals have been put forward as to how anxiety may interrupt the brain’s processing of dynamic (trial-by-trial) interoceptive predictions and/or prediction errors ( Allen, 2020 ; Barrett and Simmons, 2015 ; Brewer et al., 2021 ; Paulus, 2013 ; Paulus and Stein, 2006 , 2010 ; Paulus et al., 2019 ), these are as yet untested. Therefore, within a rigorous assessment profile, we included neuroimaging of a novel breathing-related interoceptive learning paradigm, providing the first empirical insight into the brain activity associated with interoceptive predictions and prediction errors.…”
Section: Introductionmentioning
confidence: 99%
“…As a first contribution, our results offer a nice framework to study ER strategies and their influence on affective processing, by combining insights from the process model of ER (Gross, 1998;Gross and John, 2003) with others from predictive models of emotion (Seth and Friston, 2016;Barrett, 2017). Second, given the role of altered ER (Cisler et al, 2010) and interoceptive prediction patterns (Brewer et al, 2021) as risk factors for the development of affective psychopathology, our results may provide some potential clinical implications. The assessment of the influence of ER strategies on affective processing through paradigms similar to ours could, for instance, be included among clinical practices to early detect people at risk of psychopathology.…”
Section: Discussionmentioning
confidence: 80%
“…Specifically, stroke-induced damage to the insula, compared with damage to other parts of the brain, seems to make it easier for individuals who smoke cigarettes to quit doing so. Poststroke changes in behavior and subjective experience suggest that this effect, which has been replicated in multiple studies (for a review, see Brewer et al, 2021), reflects an abrupt decline in craving caused by a disruption in interoception. For instance, a participant in the seminal study by Naqvi and his colleagues (2007) reported that he quit smoking immediately following a stroke affecting the insula because his “body forgot the urge to smoke” (p. 534).…”
Section: Affect and Interoception Are Key Elements Of Cravingmentioning
confidence: 86%